2000
DOI: 10.1007/pl00005506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on carnosine, anserine and free amino acid composition of beef broth and its role in flavour development

Abstract: In an attempt to determine the most important free amino acids (FAAs) in the development of the flavour of beef broths, the amino acid compositions of beef broths prepared at different temperatures and cooking times, with flavours of different intensities, were studied. From our data, broths obtained at temperatures above 75 7C and cooking times longer than 120 min had significantly lower levels of most of the FAAs studied (P~0.05). Statistical analysis of the sensorial and analytical data (principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
0
35
1
Order By: Relevance
“…Gravy consists of fat and water, including water-soluble compounds. Even though volatile compounds are important for the flavor of gravies, several studies have documented the very important role of small water-soluble compounds such as free amino acids, small peptides, nucleotides, small organic acids, and salts in the flavor of broth (Cambero et al, 2000a(Cambero et al, , 2000bCambero et al, 1992;Pereira-Lima et al, 2000;Schlichterle-Cerny & Grosch, 1998). It is well documented in model systems that free fatty acids reduce bitter taste (Koriyama et al, 2002;Metcalf & Vickers, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Gravy consists of fat and water, including water-soluble compounds. Even though volatile compounds are important for the flavor of gravies, several studies have documented the very important role of small water-soluble compounds such as free amino acids, small peptides, nucleotides, small organic acids, and salts in the flavor of broth (Cambero et al, 2000a(Cambero et al, , 2000bCambero et al, 1992;Pereira-Lima et al, 2000;Schlichterle-Cerny & Grosch, 1998). It is well documented in model systems that free fatty acids reduce bitter taste (Koriyama et al, 2002;Metcalf & Vickers, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…It was not possible to determine the extent to which the reductions on cooking were due to losses in cooking juices or to changes in the compounds. Pereira-Lima et al (2000) studied the effect of heating conditions on the presence of carnosine and anserine in beef broths and found a significant correlation between carnosine and anserine levels and heating temperature and time. They suggest that cooking temperature is more important than heating time in determining the concentrations of these dipeptides.…”
Section: Meatsmentioning
confidence: 97%
“…Other more recent studies (25,26) have reported on the chemical and sensory changes of meat flavor after cooking, but it is difficult to attribute these studies to the field of MG, as these cooking practices are commonly applied at industrial level and are well known topics in food science.…”
Section: Collaboration Among Chefs and Scientistsmentioning
confidence: 98%